Analysis of the Role of the School Environment in the Formation of Children's Character - Tiara Agustina; Noviana, Eddy (Yayasan Thaifah Manshurah Pekanbaru, 2023)
This study aims to determine how the role of the school environment in the formation of children's character. This type of research is descriptive qualitative. The data sources of this research are school principals and teachers. The amount of data in this research is 9 people, consisting of 1 school principal, 6 teachers from grades 1 to grade 6, teachers in Islamic religious studies and sports teachers. As for data collection techniques in this study by way of observation, interviews and documentation. Data analysis techniques that researchers use are data reduction, data presentation, and conclusions. Based on the results of the study, it was found that the role of the school environment in the formation of children's character at SDN 02 Andiang, Kec. Suliki, Kab 50 Kota, had been carried out well and some were still not good